2004
DOI: 10.1055/s-2004-824887
|View full text |Cite
|
Sign up to set email alerts
|

Should the Donor Radius be Plated Prophylactically after Harvest of a Radial Osteocutaneous Flap? A Cost-Effectiveness Analysis

Abstract: The objective of this study was to assess the cost-effectiveness of prophylactic plating of the donor radius after harvest of a radial osteocutaneous flap. Costs were measured from a Ministry of Health perspective, and effectiveness in terms of quality adjusted life years (QALYs.) A literature search identified 22 studies reporting complications of radial osteocutaneous free flaps, and nine studies reporting complications of radius plating. The rates of the various complications were pooled to provide the prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…2 Several studies have since examined the effect of prophylactic plating and demonstrated a significant reduction in the prevalence of pathologic radial fractures. [3][4][5]7,21 Despite the effectiveness of prophylactic plating, a cost-effective analysis published by Rockwell and Thoma 22 determined that prophylactic plating of the donor radius is not a costeffective method when compared to treatment of donor radius fractures after they occur. Additionally, prophylactic plating with simultaneous iliac crest bone grafting has more recently been described.…”
Section: Discussionmentioning
confidence: 99%
“…2 Several studies have since examined the effect of prophylactic plating and demonstrated a significant reduction in the prevalence of pathologic radial fractures. [3][4][5]7,21 Despite the effectiveness of prophylactic plating, a cost-effective analysis published by Rockwell and Thoma 22 determined that prophylactic plating of the donor radius is not a costeffective method when compared to treatment of donor radius fractures after they occur. Additionally, prophylactic plating with simultaneous iliac crest bone grafting has more recently been described.…”
Section: Discussionmentioning
confidence: 99%
“…Placing a plate on the donor radius is not simple or risk free (4). It adds time, complexity and cost to a procedure, which inherently consume a great deal of resources and this may not be cost effective (30). However, when a fracture occurs with fixation in place, treatment is less difficult because the fractures tend not to displace (4,5,10,27).…”
Section: Discussionmentioning
confidence: 99%
“…Sixth, it is important to exclude arteria peronea magna directly before harvest of the peroneal vessels; this is performed by inspecting the peroneal vessels for excessive size and by placing a microvascular clamp across the distal peroneal vessels early in the flap harvest to ensure maintenance of pedal pulses and absence of foot ischaemia. 30,31 The scapula donor site provides versatility regarding the soft tissue reconstruction, but the quality of the donor bone does not approach that of the fibula, and its location on the back is a major drawback since it precludes a two-team approach, prolonging the operation. Other reported donor site morbidities from fibula harvest are also generally avoidable.…”
Section: Segmental Mandibular Reconstruction: Principles and Optionsmentioning
confidence: 99%